A method of determining heated ancient nephrite jades in China - Bao, Yi (Sci Rep, 2018)
Ancient jade is one of the most significant cultural relics in China. Despite the increasingly important role of heated jades in ancient jade study, there are still few in-depth material studies on heated jades for the time being, which results in limitations on archaeological research and conservation. In order to evaluate the appearance change of nephrite jades, we employ the heating simulation experiment to present these change under different heating temperature ranging from 100 °C to 1300 °C. In this study, a nondestructive identification method proposed is to help determine whether the ancient jades were heated before and what the approximate heating temperature was from 100 °C to 1300 °C though phase transformation, structure change and colour variation with several advanced characterization methods such as the X-ray diffraction (XRD), the thermo-gravimetric analyser (TGA), the ultraviolet-visible spectrophotometer (UV-Vis), the Fourier transform infrared spectroscopy (FTIR) and the scanning electron microscope (SEM). The hierarchy of colour (from ~500 °C) and structure (from ~800 °C) on heated jades in the jade research field were first proposed and discuss here. This method is considered useful and valuable in the study and protection of Chinese ancient jades.